Gender differences in the association between adverse childhood experiences and impulsivity in Saudi Arabian adults: A cross-sectional study - Saleh A. Alghamdi (PLoS ONE, 2026)
Background Adverse childhood experiences (ACEs) are linked to impulsivity, a transdiagnostic risk factor for psychopathology. However, gender differences in ACE-impulsivity pathways remain unclear, particularly in Middle Eastern populations, and prior research has often conflated differential exposure with differential vulnerability while lacking rigorous multiple testing corrections. Objective This study examined gender differences in ACE exposure, multidimensional impulsivity, and ACE-impulsivity associations in Saudi Arabian adults, distinguishing between differential exposure and differential vulnerability hypotheses using rigorous statistical methods. Methods A nationwide cross-sectional online survey recruited 379 Saudi adults (222 female, 157 male; majority aged 18–25 years [55.7%]). Participants completed the Arabic 10-item ACE questionnaire and Short UPPS-P Impulsive Behavior Scale (five dimensions: Negative Urgency, Positive Urgency, Sensation Seeking, Lack of Premeditation, Lack of Perseverance). Analyses employed Benjamini-Hochberg false discovery rate (FDR) correction (q = .05) across test families, bootstrap confidence intervals (5,000 iterations) for all effect sizes, and hierarchical regression models testing Gender × ACE interactions with demographic covariates. Results Females reported significantly higher ACE exposure (M = 2.24 vs. 1.75, p = .005), concentrated in emotional neglect (35.1% vs. 17.8%, FDR-significant) and household mental illness (29.3% vs. 16.6%, FDR-significant). No impulsivity dimension showed significant gender differences after FDR correction. Gender-stratified analyses revealed significant ACE correlations for four dimensions in females (ρ = 0.142–0.262) but only Negative Urgency in males (ρ = 0.222). However, bootstrap tests of cross-gender correlation differences were all non-significant (all Δρ 95% CIs included zero). Covariate-adjusted Gender × ACE interactions were uniformly null (all p > .16, ΔR² < 0.005). Conclusions Gender differences in ACE-impulsivity associations reflect differential exposure (higher female ACE burden) rather than differential vulnerability (different per-ACE impact). Findings support universal trauma-informed interventions with ACE-type-specific modifications rather than fundamentally gender-differentiated approaches. Results highlight the importance of rigorous statistical controls and distinction between exposure and vulnerability in ACE research.